k-step Reachability Query Processing on Label-constrained Graph - Du, Ming; Xing, Rui-ping; Zhou, Jun-feng; Tan, Yu-ting (Ji suan ji ke xue, 2022)
The k-step reachability query processing on label-constrained graph is used to answer whether there is a path with a length not greater than k between two points and the labels on this path are in the specified label set.The k-step reachability query processing on label-constrained graph is widely used in reality, but there is no relevant algorithm to answer it.Therefore, the LK2 H algorithm is proposed firstly.LK2 H algorithm mainly consists of two steps.The first step is to build a pair of 2-Hop in-dexes containing k and label information for all vertices on the graph, and the second step is querying based on the built index.In order to return information as much as possible to the user, LK2 H optimizes the results of a type of unreachable query: when the user cannot specify all the label types, and cannot give full label constraints resulting in unreachable query results, the complete label set will return to the user.Secondly, an optimization algorithm, LK2 H+,is proposed.LK2 H+ algorithm further reduces